2018
DOI: 10.1042/etls20180042
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoactivation of Wnt/β-catenin pathways in health and disease

Abstract: Mechanical forces play an important role in regulating tissue development and homeostasis in multiple cell types including bone, joint, epithelial and vascular cells, and are also implicated in the development of diseases, e.g. osteoporosis, cardiovascular disease and osteoarthritis. Defining the mechanisms by which cells sense and respond to mechanical forces therefore has important implications for our understanding of tissue function in health and disease and may lead to the identification of targets for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 72 publications
1
7
0
1
Order By: Relevance
“…affected. Involvement of Wnt/β-catenin signaling in the pathogenesis of AC (Garcia-Gras et al, 2006) and the ability of mechanotransduction to activate canonical Wnt/β-catenin signaling (Warboys, 2018) was also confirmed in zebrafish. Furthermore, other authors demonstrated that YAP/TAZ play a central role in delivering information of mechanical environments surrounding cells to the nucleus transcriptional machinery suggesting a link between mechanotransduction and hippo pathway (Dobrokhotov et al, 2018).…”
Section: Physical Exercise and Mechanical Load In Ac Animal Modelsmentioning
confidence: 73%
“…affected. Involvement of Wnt/β-catenin signaling in the pathogenesis of AC (Garcia-Gras et al, 2006) and the ability of mechanotransduction to activate canonical Wnt/β-catenin signaling (Warboys, 2018) was also confirmed in zebrafish. Furthermore, other authors demonstrated that YAP/TAZ play a central role in delivering information of mechanical environments surrounding cells to the nucleus transcriptional machinery suggesting a link between mechanotransduction and hippo pathway (Dobrokhotov et al, 2018).…”
Section: Physical Exercise and Mechanical Load In Ac Animal Modelsmentioning
confidence: 73%
“…Activated FAK phosphorylates AKT at Ser473, and AKT phosphorylates GSK3β at Ser9. β-Catenin is then free to translocate into the nucleus (43)(44)(45). To validate this signaling pathway, we measured protein levels.…”
Section: Cd93 Regulates the Fate Determination Of Radial Glial Cells Inmentioning
confidence: 99%
“…The Wnt signalling pathway is known to regulate responses to mechanical forces in non-vascular mechanoresponsive cells 8 . Transcriptomic analysis reveals that Wnt pathway genes are significantly enriched in EC exposed to atherogenic flow environments 9,10 suggesting a possible role in promoting flow-mediated EC dysfunction 10 .…”
Section: Introductionmentioning
confidence: 99%